Hubungan Knowledge Management Dengan Kinerja Perawat Di Ruang Rawat Inap Rumah Sakit Stella Maris (Window of Public Health Journal, 2026)
Nurses comprise the largest number of healthcare workers in hospitals and play a crucial role in maintaining service quality, particularly in inpatient wards, which involve high levels of patient interaction. Stella Maris Hospital Makassar employs 134 inpatient nurses, but only a small proportion have received formal training from the hospital. Despite this, there are efforts to share knowledge internally among nurses. This study aims to clarify how knowledge management influences nurse performance in inpatient wards at Stella Maris Hospital, providing insights to improve care quality. This study used a quantitative, cross-sectional design. Purposive sampling was used, and the sample size was determined using the Slovin formula, resulting in 100 respondents, all inpatient nurses. Data analysis was performed using the chi-square test. The results showed no relationship between knowledge management dimensions and nurse performance, including socialization (p = 0.086), externalization (p = 0.361), combination (p = 0.209), and internalization (p = 0.279). While these findings may seem conclusive, they highlight the importance of further exploration. Recognizing the complexity of nurse performance can motivate professionals to consider additional factors influencing outcomes in the inpatient ward of Stella Maris Hospital, Makassar. Based on the study's findings, the hospital is encouraged to enhance its knowledge management system by strengthening a culture of information sharing, documenting work experiences, and providing training. These steps can empower nurses to better manage and apply their knowledge, ultimately improving the quality of nursing care and inspiring continuous improvement.